2011
DOI: 10.1007/s00404-011-1912-z
|View full text |Cite
|
Sign up to set email alerts
|

PAPP-A levels of late pregnancy in preeclampsia and HELLP syndrome

Abstract: PAPP-A level at last trimester increases in all mild-severe preeclampsia and HELLP syndrome, but is not predictive for severity of preeclampsia or HELLP syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The increase in serum free β-hCG, which has vasodilatory properties, observed during and in the few weeks prior to the development of the clinical signs of PE, has been attributed to hypoxia-induced hypersecretion to counteract the generalized vasoconstriction which characterizes PE [10,11,12,13,39,40]. The reported paradoxical behaviour of serum PAPP-A in PE with decrease at 11-13 weeks and increase at the time of PE [4,14,15,16,17,18,19] could be the consequence of impaired placental function for the former and global activation of inflammation for the latter. Our finding that serum PAPP-A at 30-33 weeks is normal suggests that the increase in this metabolite does not precede but coincides with the clinical onset of PE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in serum free β-hCG, which has vasodilatory properties, observed during and in the few weeks prior to the development of the clinical signs of PE, has been attributed to hypoxia-induced hypersecretion to counteract the generalized vasoconstriction which characterizes PE [10,11,12,13,39,40]. The reported paradoxical behaviour of serum PAPP-A in PE with decrease at 11-13 weeks and increase at the time of PE [4,14,15,16,17,18,19] could be the consequence of impaired placental function for the former and global activation of inflammation for the latter. Our finding that serum PAPP-A at 30-33 weeks is normal suggests that the increase in this metabolite does not precede but coincides with the clinical onset of PE.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that the altered levels of these metabolites may be apparent from the first trimester of pregnancy. Serum free β-hCG is increased in PE but at 11-13 weeks it is decreased or not altered [4,10,11,12,13,14], PAPP-A is increased in PE but reduced at 11-13 weeks [4,14,15,16,17,18,19] and PlGF is reduced in both established PE and in the first trimester [4,20,21,22,23,24,25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Given its mechanism for inhibition of IGF action during pregnancy, a direct relationship between maternal PAPP-A and infant anthropometric parameters may have been expected. In some studies, a positive correlation was found; however, other investigators have observed no association between maternal protein A and birth weight [10, 12, 20, 21, 30, 31]. Most surprisingly, Senses et al [4] found a significant negative correlation between PAPP-A levels and birth weight, but the authors measured this protein level only in cord blood and speculated that this protein affected the length of newborns more strongly than weight.…”
Section: Discussionmentioning
confidence: 99%
“…At present, serum level of PAPP-A are widely used in prenatal screening as an indicator of certain genetic disorders in the fetus [710]. However, recent studies documented that pregnancy-associated plasma protein A modulates insulin-like growth factor (IGF) bioavailability by specific cleavage of antagonizing IGF-binding protein (IGFBP), especially IGFBP-4 and IGFBP-5, and thereby may promote fetal growth and development [5, 11, 12]. Low concentrations of PAPP-A during gestation may result in inadequate expression of insulin-like growth factors in the syncytiotrophoblast leading to utero-placental insufficiency, and can be a risk factor for many health complications for the mother and child [1217].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation